Gene–disease relationship evidence: A clinical perspective focusing on ultra‐rare diseases. Issue 8 (24th March 2022) - Santen, Gijs W. E.; Leitch, Harry G.; Cobben, Jan
Abstract: The ACMG framework for variant interpretation is well‐established and widely used. Although formal guidelines have been published on the establishment of the gene–disease relationships as well, these are not nearly as widely acknowledged or utilized, and implementation of these guidelines is lagging. In addition, for many genes so little information is available that the framework cannot be used in sufficient detail. In this manuscript, we highlight the importance of distinguishing between phenotype‐first and genotype‐first gene–disease relationships. We discuss the approaches currently available to establish gene–disease relationships and suggest a checklist to assist in evaluating gene–disease relationships for genes with very little available information. Several real‐life examples from clinical practice are given to illustrate the importance of a thorough thought process on gene–disease relationships. We hope that these considerations and the checklist will provide help for clinicians and clinical scientists faced which variants in genes without robustly ascertained gene–disease relationships. Abstract : A clinician's checklist to judge gene‐disease relationships for ultra‐rare disease.